STUDENT'S ATTITUDE TOWARDS MATHEMATICS AT THE UNIVERSITY OF ÉVORA, PORTUGAL - Bayudan, Kenny J (2015)
Mathematics is generally everywhere. Its laws can be observed in the most basic living organism to the very complex nature of the universe. The importance of learning mathematics during undergraduate training cannot be understated as it is necessary for students to understand the rudiments and complexity of the world around us. It follows that as they study mathematics, it is important that they maintain a favorable attitude towards math. Attitude influences not only how a person perceives the world around him but also how he interprets situations, circumstances and actions of others. Hence, a more positive attitude has to be developed among university students at an early stage to enable them to make the right choices and decisions in life and in learning. This study is an attempt to determine the attitude of freshmen student who are taking a math subject in the fall semester of the academic year 2013-2014 at the University of Évora, Portugal. A questionnaire was developed, which underwent item, factor and reliability analyses, and used to gather data about students’ attitude towards math and their motivation, interest, perceived competence and anxiety levels. The results of this research show that freshmen students initially have positive attitude towards math prior to commencing university formation. There is a strong positive correlation between attitude and the motivation and interest, perceived competence and anxiety subscales. As far as the researcher’s knowledge concerned, this is the first time that attitude of freshmen students in the said university is investigated. This assessment is important to the university faculty and administration as it raises concern on the affective aspect of learning. It also helps them to understand the disposition of their students in math and create possible means of intervention to help those with a negative attitude towards the subject.